Pengolahan Limbah Kulit Pisang Menjadi Sabun - Zain, Irsyadi; T. Arief Pahlevi Pasha; Salshadila, Nur (Anotero Lembaga Scientific Pekanbaru, 2023)
Garbage is something left over from the daily activities of humans and nature that has not or no longer has the benefit of being used again. Pekanbaru City is one of the cities in Riau Province. Pekanbaru City has a population of 994,585 in 2021. With the existing population, Pekanbaru City is one of the cities that has a lot of waste generation. The annual amount of waste generation in Pekanbaru City is 1,488,423.65 tons. There are various types of waste in Pekanbaru City, food waste is the biggest contributor to waste generation in Pekanbaru City, one example is banana peel waste. Banana peel has some very good ingredients for the skin. The purpose of this research is to reduce waste in Pekanbaru City by making a business from banana peel waste which is processed into soap. The method used in this research is descriptive method with a qualitative approach and primary studies. The results of the research show that based on the Business Model Canvas and SWOT Analysis, creating a business from banana peel waste which is processed into soap can reduce the amount of waste in Pekanbaru City, especially banana peel waste